Communication and technology in genetic counseling for familial cancer. (20th December 2013) - Lynch, H.T.; Snyder, C.; Stacey, M.; Olson, B.; Peterson, S.K.; Buxbaum, S.; Shaw, T.; Lynch, P.M.
<x xml:space="preserve">Abstract</x> When a cancer predisposing germline mutation is detected in an index case, the presence of the underlying syndrome is confirmed and the potential for predictive testing of at‐risk relatives is established. However, the reporting of a positive family history does not routinely lead to communication of information about risk to close, much less distant relatives. This review summarizes information technology utilized to address penetration or 'reach' of knowledge of risk within extended families, including the use of telephone and video counseling to reach distant patients, and anticipate novel internet‐based processes for communication between investigators and relatives.